The Negative Intelligence–Religiosity Relation: New and Confirming Evidence. (June 2020) - Zuckerman, Miron; Li, Chen; Lin, Shengxin; Hall, Judith A.
Zuckerman et al. (2013) conducted a meta-analysis of 63 studies that showed a negative intelligence–religiosity relation (IRR). As more studies have become available and because some of Zuckerman et al.'s (2013) conclusions have been challenged, we conducted a new meta-analysis with an updated data set of 83 studies. Confirming previous conclusions, the new analysis showed that the correlation between intelligence and religious beliefs in college and noncollege samples ranged from −.20 to −.23. There was no support for mediation of the IRR by education but there was support for partial mediation by analytic cognitive style. Thus, one possible interpretation for the IRR is that intelligent people are more likely to use analytic style (i.e., approach problems more rationally). An alternative (and less interesting) reason for the mediation is that tests of both intelligence and analytic style assess cognitive ability. Additional empirical and theoretical work is needed to resolve this issue.